Composite polishing solution for laser additive manufacturing alloy material and polishing method of composite polishing solution
By using composite polishing liquid composed of H3PO4-HCl-HNO3 and other components in SLM additive manufacturing, combined with multi-stage polishing treatment, the problem of high roughness of SLM printing special-shaped alloy materials is solved, and more efficient The polishing effect significantly improves the smoothness and brightness of the alloy material.
Patent Information
- Application Number
- CN202411301682.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-18
AI Technical Summary
When printing complex special-shaped alloy materials with SLM additive manufacturing, there is a problem of excessive roughness. The existing polishing liquid treatment effect is not ideal, especially the traditional quaternary acid system with strong acid, alkaline and HF-added quaternary acid system cannot effectively improve the surface smoothness. and brightness.
Provide a composite polishing liquid, including mixed acid solution (H3PO4-HCl-HNO3), masking agents (such as EDTA, citric acid) and surfactants (such as sodium fatty alcohol ether sulfate, betaine type amphoteric surfactant), by Pretreatment and multi-stage polishing methods, combined with stirring conditions, achieve a more uniform and controllable polishing effect.
It significantly reduces the roughness of the surface of the alloy material, improves the smoothness and brightness, avoids unnecessary corrosion, enhances the selectivity and efficiency of the polishing liquid, and is suitable for polishing treatment of complex-shaped alloy materials.
Smart Images

Figure CN119243162A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy material polishing, and in particular to a composite polishing liquid for laser additive manufacturing alloy material and a polishing method thereof. Background Art
[0002] SLM additive manufacturing, or selective laser melting technology, is a cutting-edge 3D printing method. Since SLM additive manufacturing can achieve high-precision manufacturing, has the characteristics of a wide range of material selection and rapid prototyping, it has significant advantages in saving resources and reducing waste. It can minimize the waste of raw materials and is widely used in the preparation of alloy materials.
[0003] However, additive manufacturing is not "free" manufacturing, and the forming capacity of the equipment is affected by many factors. Taking SLM as an example, the overhanging structure whose angle between the surface and the horizontal direction is lower than the critical value requires support material, and this critical value is usually 45°. From the principle of additive manufacturing and the raw materials used, it can be seen that when processing the overhanging part, its lower layer is powder and other materials, which cannot provide it with sufficient support and heat transfer path, and the structure is prone to collapse or warping. Although adding support structures can solve these problems, it means additional material loss, increased forming time and post-processing work, and may also affect the internal stress distribution of the part. When measuring the surface roughness of the upper and lower epidermis of inclined thick-walled samples, the following is usually observed: as the angle θ (the angle between the lower surface of the sample and the printing base) decreases, the roughness of the lower surface increases. Therefore, when using SLM additive manufacturing to print complex special-shaped alloy materials, there is often a problem of excessive roughness.
[0004] After polishing with the traditional polishing system, the smoothness and brightness of the sample are still lacking, and the roughness of the sample has not been significantly improved. This is mainly because under strong acid corrosion, the surface will quickly become over-corroded, and the raised parts cannot be selectively corroded, so the roughness cannot be reduced. In addition, the existing hydrogen peroxide system, alkaline system and HF-added four-acid system all have unsatisfactory results. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a composite polishing liquid for laser additive manufacturing alloy materials and a polishing method thereof, so as to solve the technical problem that the roughness of complex special-shaped alloy materials printed by SLM additive manufacturing is too large and the polishing effect after polishing with existing polishing liquid is poor.
[0006] The purpose of the present invention is mainly achieved through the following technical solutions:
[0007] In one aspect, the present invention provides a composite polishing liquid for laser additive manufacturing of alloy materials, the composite polishing liquid comprising a mixed acid solution, a masking agent, a stabilizer and a surfactant;
[0008] The mixed acid solution is H 3 PO 4 -HCl-HNO 3 ;
[0009] The mass ratio of the mixed acid solution, the masking agent, the stabilizer and the surfactant is 1L: 5-8g: 12-18g: 2-5g.
[0010] In one possible design, H 3 PO 4 Solution, HCl solution, HNO 3 The volume ratio of the solution is 1:(6.5~7.7):(3.5~4.5).
[0011] In one possible design, H 3 PO 4 The volume concentration of the solution is 80-85%;
[0012] The mass concentration of HCl solution is 1.15-1.2 g / mL; HNO 3 The mass concentration of the solution is 1.4-1.45 g / mL.
[0013] In one possible design, the mixed acid H 3 PO 4 -HCl-HNO 3 The preparation method is to 3 PO 4 Solution, HCl solution, HNO 3 The solutions were mixed sequentially.
[0014] In one possible design, the masking agent includes one or more of EDTA, citric acid and tartaric acid.
[0015] In one possible design, in step 2, the stabilizer includes one or more of ethanol, ethylene glycol, propylene glycol and diethylene glycol.
[0016] In a possible design, the surfactant includes one or more of sodium fatty alcohol ether sulfate, betaine type amphoteric surfactant and sodium dodecylbenzene sulfonate.
[0017] On the other hand, the present invention also provides a polishing method for laser additive manufacturing alloy materials, using the above-mentioned composite polishing liquid; the polishing method comprises the following steps:
[0018] Step 1, pre-treating the surface of the laser additively manufactured alloy material;
[0019] Step 2, measuring the mass and roughness of the sample before chemical polishing, and observing its morphology with a microscope;
[0020] Step 3: Mix the laser additive manufacturing alloy material after surface pretreatment with the composite polishing liquid, and perform polishing treatment to achieve polishing of the laser additive manufacturing alloy material.
[0021] Further, in step 1, the pretreatment includes cleaning, degreasing and water washing performed in sequence.
[0022] Furthermore, the laser additive manufacturing alloy material includes GH3536 alloy or GH4169 alloy.
[0023] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0024] (1) The present invention uses a mixed acid solution to corrode the protrusions on the surface of the laser additively manufactured alloy material (unmelted powder on the sample surface, including impurities such as slag and molten balls) to improve the surface flatness of the alloy material and reduce the roughness.
[0025] (2) The present invention forms a protective layer by covering the concave part of the workpiece surface with a masking agent and a surfactant, which can effectively prevent the acidic components in the composite polishing liquid from contacting the alloy in the concave part, thereby preventing unnecessary corrosion. In addition, the masking agent also slows down the speed of the corrosion reaction, avoiding excessive corrosion, thereby achieving a more uniform and controllable polishing effect. The surfactant can also improve the distribution and wettability of the composite polishing liquid on the workpiece surface, reduce the corrosion effect on the non-convex part, and increase the polishing effect on the convex part, which helps to improve the selectivity of polishing, so that the polishing liquid can act more accurately on the convex part, thereby achieving a better polishing effect.
[0026] (3) The present invention can reduce the roughness of the alloy surface through the composite polishing liquid, thereby improving the smoothness and brightness of the alloy material.
[0027] (4) Compared with common chemical polishing liquid, the composite polishing liquid disclosed in the present invention has the selectivity for polishing the protrusions on the surface of alloy materials, can avoid excessive corrosion, and achieve a more uniform and controllable polishing effect; the polishing method is simple and easy to implement, with high polishing efficiency, and is suitable for promotion and application.
[0028] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the embodiments of the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0030] Figure 1a FIG1 is a comparison diagram of the fuel nozzle head component of the present invention before and after polishing;
[0031] Figure 1b Comparison of the fuel nozzle head component of the present invention before and after polishing Figure 2 ;
[0032] Figure 1c FIG1 is a comparison diagram of the fuel nozzle integral component of the present invention before and after polishing;
[0033] Figure 1d Comparison of the fuel nozzle integral component of the present invention before and after polishing Figure 2 ;
[0034] Figure 2 This is a surface morphology diagram of the fuel nozzle head component of the present invention before polishing;
[0035] Figure 3 This is a surface morphology diagram of the fuel nozzle head component after polishing of the present invention. DETAILED DESCRIPTION
[0036] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0037] In one aspect, the present invention provides a composite polishing liquid for laser additive manufacturing of alloy materials; the composite polishing liquid comprises a mixed acid solution, a masking agent, a stabilizer and a surfactant; the mixed acid solution is H 3 PO 4 -HCl-HNO 3 The mixed acid solution is composed of H 3 PO 4 , HCl and HNO 3 The mixed solution; the mass ratio of the mixed acid solution, the masking agent, the stabilizer and the surfactant is 1L: 5-8g: 12-18g: 2-5g.
[0038] In the above-mentioned mixed acid solution, hydrochloric acid mainly plays the role of dissolving metals, but the dissolution effect of hydrochloric acid alone on the alloy surface is not very significant. When hydrochloric acid is combined with nitric acid, its dissolving ability is enhanced and the oxide layer on the alloy surface can be removed; by adding phosphoric acid to the mixed acid solution, the excessive dissolution of the alloy surface can be effectively inhibited.
[0039] It should be noted that in the above mixed acid solution, phosphoric acid (H 3PO 4 ) + Ions can promote the initial dissolution of the alloy; phosphoric acid is a polyacid, and the H + Ions can react with metal surfaces and promote the dissolution of metal oxides. + Ions can also control the dissolution rate; although H + The H ions promote the initial dissolution of metal oxides on the alloy surface, but as the metal surface oxides are removed, + ions will also be gradually consumed, followed by H + As the ion concentration decreases, the rate of continued dissolution of the metal surface will also decrease accordingly, thereby slowing down the dissolution rate and preventing excessive dissolution. 4 3- ): (1) Phosphate ion (PO 4 3- ) can form a protective film on the metal surface; when the metal surface is slightly oxidized, phosphate ions can combine with metal ions to form phosphate compounds, which can form a protective layer on the metal surface to prevent further dissolution. (2) Phosphate ions (PO 4 3- ) can adjust the pH value of the solution; phosphoric acid is a weak acid that can gradually dissociate in the solution. + The presence of phosphate ions can act as a buffer to help maintain the pH value of the solution within a relatively stable range. This helps to maintain a suitable dissolution environment, neither too acidic to cause rapid dissolution nor too alkaline to stop dissolution. (3) Phosphate ions (PO 4 3- ) can promote passivation; phosphate ions can help form a dense oxide film on the metal surface, that is, phosphate ions can help form a passivation layer on the metal surface. The passivation layer can effectively prevent the further reaction of the metal with the surrounding medium, thereby inhibiting the further dissolution of the metal.
[0040] In summary, in the mixed acid solution of the present invention, phosphoric acid can not only promote the initial dissolution in the metal surface treatment, but also inhibit excessive dissolution by forming a protective film and adjusting the pH value, and has a dual role. By adding phosphoric acid to the mixed acid solution, the metal surface can be protected from damage caused by excessive dissolution while removing the oxide layer.
[0041] From the above analysis, it can be seen that the mixed acid solution of the present invention has the following effects: (1) dissolving effect: the mixed acid solution reacts chemically with the metal surface to dissolve the oxide layer or impurities on the metal surface, thereby achieving the purpose of removing surface defects; (2) uniform corrosion: through a reasonable ratio (H 3 PO4 Solution, HCl solution, HNO 3 The volume ratio of the solution is 1: (6.5-7.7): (3.5-4.5). The mixed acid solution can produce uniform micro-corrosion on the metal surface, which helps to remove the microscopic uneven parts of the surface and make the surface smoother; (3) Improve polishing efficiency: The mixed acid solution can accelerate the dissolution rate of the metal surface, speed up the polishing process, and improve production efficiency.
[0042] In the above composite polishing liquid, the mass ratio of the mixed acid solution, the masking agent, the stabilizer and the surfactant is 1L: 5-8g: 12-18g: 2-5g.
[0043] Compared with the prior art, the present invention has a better polishing effect by controlling the mixed acid solution, masking agent, stabilizer and surfactant within the above range, can significantly reduce the roughness of the alloy material surface, and improve the flatness of the alloy material surface.
[0044] It should be noted that the mass ratio of the mixed acid solution, the masking agent, the stabilizer and the surfactant is 1L: 6-7g: 13-16g: 3-4g.
[0045] Furthermore, in the above-mentioned composite polishing liquid, the mass ratio of the mixed acid solution, the masking agent, the stabilizer and the surfactant is 1L:6.5g:15g:3.5g.
[0046] The masking agent in the composite polishing liquid has the following functions: (1) Selective protection: The masking agent can selectively adsorb on specific areas of the metal surface (for example, the concave part of the workpiece surface) to prevent these areas from being corroded by the acid solution, thereby protecting specific parts of the workpiece from damage. (2) It can improve the surface quality of the alloy material: Through the effect of the masking agent, it can avoid over-polishing or corrosion spots in specific areas, which helps to improve the surface quality of the final product.
[0047] The stabilizer in the composite polishing liquid has the following functions: (1) Preventing chemical changes: The stabilizer can prevent the components of the composite polishing liquid from changing during use, such as preventing the acidic components from volatilizing or decomposing, thereby maintaining the effectiveness and stability of the polishing liquid. (2) Prolonging the service life of the composite polishing liquid: By maintaining the chemical stability of the polishing liquid, the stabilizer can prolong the service life of the composite polishing liquid, reduce the frequency of replacement, and reduce costs.
[0048] The surfactants in the composite polishing liquid have the following functions: (1) Improve wettability: The surfactant can reduce the surface tension of the liquid, making it easier for the composite polishing liquid to form a uniform film on the metal surface, thereby improving the wettability and coverage of the polishing liquid. (2) Dispersion and suspension: The surfactant helps to disperse the metal ions and other impurities generated during the polishing process, preventing them from redepositing on the metal surface and causing secondary pollution. (3) Improve the cleaning effect: Through the emulsification effect of the surfactant, the surfactant can disperse and suspend pollutants such as oil in the polishing liquid, facilitating the subsequent cleaning process.
[0049] In summary, the components of the composite polishing liquid of the present invention, namely, the mixed acid solution, the masking agent, the stabilizer and the surfactant, each play a different role in the metal surface polishing process, and these components work together to ensure the polishing effect.
[0050] In order to control the corrosion rate of the composite polishing liquid and obtain a good polishing effect, the mixed acid H of the present invention 3 PO 4 -HCl-HNO 3 Middle, H 3 PO 4 Solution, HCl solution, HNO 3 The volume ratio of the solution is 1:(6.5~7.7):(3.5~4.5).
[0051] Furthermore, H 3 PO 4 Solution, HCl solution, HNO 3 The volume ratio of the solution is 1:7:4.
[0052] In the above mixed acid, H 3 PO 4 The volume concentration of the solution is 80-85%, for example, 81%, 82%, 83%, 84%, 85%.
[0053] In the above mixed acid, the mass concentration of HCl solution is 1.15-1.2 g / mL, for example, 1.16 g / mL, 1.17 g / mL, 1.18 g / mL, 1.19 g / mL; too high a concentration of hydrochloric acid will cause excessively rapid corrosion, while too low a concentration of hydrochloric acid will not meet the corrosion requirements, therefore, the mass concentration of hydrochloric acid is controlled within the above range.
[0054] In the above mixed acid, HNO 3 The mass concentration of the solution is 1.4 to 1.45 g / mL, for example, 1.41 g / mL, 1.42 g / mL, 1.43 g / mL, 1.44 g / mL.
[0055] It should be emphasized that the mixed acid solution (H 3PO 4 -HCl-HNO 3 ) is prepared by 3 PO 4 Solution, HCl solution, HNO 3 The solution was mixed.
[0056] Specifically, strictly follow the steps of first adding phosphoric acid (H 3 PO 4 ), followed by hydrochloric acid (HCl), and finally nitric acid (HNO 3 ) in the order of addition. This is because: (1) it can control the exothermic reaction: phosphoric acid is a relatively mild acid with a low heat of solution. Adding phosphoric acid first can provide a more stable environment and help control the heat release caused by the subsequent addition of acid. (2) it can reduce the generation of dangerous gases: nitric acid is a strong oxidant and will produce toxic chlorine gas (Cl 2 ), if hydrochloric acid is added first and then nitric acid, a large amount of chlorine may be generated rapidly. Therefore, adding phosphoric acid first, then carefully adding hydrochloric acid, and finally slowly adding nitric acid can avoid this dangerous situation. (3) Improve the safety of mixing: Due to the strong oxidizing property of nitric acid, it may produce a violent reaction when mixed with hydrochloric acid. Adding hydrochloric acid to phosphoric acid first and then slowly adding nitric acid can reduce this risk. At the same time, the presence of phosphoric acid can also help buffer the pH value of the system, thereby slowing down the reaction rate.
[0057] The masking agent includes one or more of EDTA, citric acid and tartaric acid. By accurately controlling the amount of the masking agent, it can be ensured that it effectively plays a masking role and avoids the negative impact of poor polishing effect and prolonged polishing time during the polishing process.
[0058] The stabilizer can play a stabilizing role. The stabilizer includes one or more of ethanol, ethylene glycol, propylene glycol and diethylene glycol. The stabilizer is used to improve the stability of the composite polishing liquid.
[0059] The surfactant includes one or more of sodium fatty alcohol ether sulfate, betaine type amphoteric surfactant and sodium dodecylbenzene sulfonate.
[0060] In summary, compared with the prior art, the present invention forms a protective layer by covering the concave part of the workpiece surface with a masking agent and a surfactant, which can effectively prevent the acidic components in the composite polishing liquid from contacting the alloy in the concave part, thereby preventing unnecessary corrosion. In addition, the masking agent also slows down the speed of the corrosion reaction, avoiding excessive corrosion, thereby achieving a more uniform and controllable polishing effect. The surfactant can also improve the distribution and wettability of the composite polishing liquid on the workpiece surface, reduce the corrosion effect on the non-convex part, and increase the polishing effect on the convex part, which helps to improve the selectivity of polishing, so that the polishing liquid can act more accurately on the convex part, thereby achieving a better polishing effect.
[0061] In addition, the present invention can reduce the roughness of the alloy surface through the composite polishing liquid, thereby improving the smoothness and brightness of the alloy material. In addition, the chemical polishing method of the present invention is simple and easy to implement, has high polishing efficiency, and is suitable for popularization and application.
[0062] On the other hand, the present invention also provides a chemical polishing method for laser additive manufacturing alloy materials, comprising the following steps:
[0063] Step 1, pre-treating the surface of the sample (laser additive manufacturing alloy material);
[0064] In the above step 1, the surface pretreatment includes cleaning, degreasing and water washing in sequence.
[0065] In the above step 1, clean water is used for washing for 15 minutes; then, ultrasonic degreasing is performed using acetone for 15 minutes, then degreasing is performed using alcohol for 15 minutes, and finally washing is performed with water.
[0066] Step 2, measuring the roughness of the sample before chemical polishing, and observing its morphology with a microscope;
[0067] Step 3, quickly putting the laser additive manufacturing alloy material after surface pretreatment into the composite polishing liquid for polishing treatment, and after completion, the laser additive manufacturing alloy material is polished;
[0068] Step 4: Perform performance test on the polished sample and measure the roughness and surface morphology of the sample;
[0069] Step 5: Record data and analyze results.
[0070] In the above step 3, the polishing process includes polishing at normal temperature, polishing at heating, polishing at high temperature and polishing at normal temperature in sequence. The polishing temperature at normal temperature is room temperature, and the polishing time is 30-60 minutes; the polishing temperature at heating is 40℃-60℃, and the polishing time is 30-60 minutes; the polishing temperature at high temperature is 80℃-120℃, and the polishing time is 20-40 minutes; the polishing temperature at normal temperature is room temperature, and the polishing time is 15-30 minutes.
[0071] It should be noted that during the polishing process, the heating rate from polishing in the normal temperature section to polishing in the heating section is 1℃ / min-3℃ / min; the heating rate is controlled within this range to slowly heat up, which helps to reduce the internal stress of the material and avoid surface defects or cracks caused by rapid heating. The heating rate from polishing in the heating section to polishing in the high temperature section is 2℃ / min-4℃ / min, the purpose of which is to ensure that the material has enough time to adapt to temperature changes and avoid thermal shock damage caused by too fast heating. The cooling rate from polishing in the high temperature section to polishing in the normal temperature section is 1℃ / min-2℃ / min. Slow cooling also helps to reduce residual stress in the material, ensure the dimensional stability of the workpiece, and improve the surface quality.
[0072] Compared with the prior art, the present invention can improve the surface quality of the workpiece by implementing a multi-stage polishing process: through polishing processes at different temperatures, the surface of the material can be gradually refined, ultimately achieving a higher flatness and glossiness. Second, it can control the surface stress of the workpiece: controlling the temperature change in stages can effectively manage the stress generated inside the material and avoid deformation or cracking of the workpiece. Furthermore, it can enhance the durability of the workpiece: appropriate temperature treatment helps to improve the mechanical properties of the material and make the finished product more durable. Finally, it can optimize the polishing efficiency: reasonable arrangement of polishing time and temperature can improve production efficiency while ensuring quality.
[0073] In order to make the components of the composite polishing liquid more uniform, in the above step 3, the polishing process is performed under stirring conditions or disturbance conditions, for example, the stirring rate of the composite polishing liquid is 100 to 500 rpm.
[0074] In summary, the composite polishing liquid and polishing method of the present invention can reduce the roughness of the alloy surface and improve the smoothness and brightness of the alloy material; Figures 1a to 1d as well as Figure 2 and Figure 3 As shown; among them, Figure 1a and Figure 1b This is a comparison of the fuel nozzle head component before and after electrochemical polishing; Figure 1c and Figure 1d This is a comparison of the fuel nozzle component before and after electrochemical polishing;
[0075] Figure 2 This is a surface morphology diagram of the fuel nozzle head component of the present invention before polishing; Figure 3 This is a surface morphology diagram of the fuel nozzle head component after polishing of the present invention; Figure 1a to Figure 1d as well as Figure 2 and Figure 3 It can be seen that the polishing effect of the present invention is very obvious, the surface brightness of the workpiece is increased, and the roughness of the alloy workpiece is reduced.
[0076] The laser additive manufacturing alloy material of the present invention comprises GH3536 high temperature special-shaped alloy material and GH4169 high temperature special-shaped alloy material. The components and mass percentages of the GH3536 high temperature special-shaped alloy material are as follows: Cr 19.5%-21.2%, Mo 8.02%-10.4%, Fe 17.79%-19.4%, Co 1.32%-1.54%, C 0.11%-0.13%, W0.55%-0.71%, Mn 0.02%-0.03%, Si 0.3%-0.35%, and the rest is Ni.
[0077] In addition, the components and mass percentage of the GH3536 high-temperature special-shaped alloy material are: Cr 20.5%, Mo9.02%, Fe 18.79%, Co 1.52%, C 0.12%, W 0.6%, Mn 0.02%, Si 0.3%, and the rest is Ni; the molding equipment model is SLM-100, used in a nitrogen protection environment, with a laser power of 200W, a scanning speed of 1000mm / s, a layer thickness of 30μm, a scanning spacing of 60μm, a zigzag line-by-line scanning strategy, and a deflection angle of 67° between adjacent layers.
[0078] Example 1
[0079] The laser additively manufactured GH3536 alloy workpiece (fuel nozzle head component and fuel nozzle overall component) was cleaned, then placed in an acetone solution for ultrasonic cleaning and degreasing, and then degreasing with alcohol. After degreasing, it was washed with water and dried to complete the surface pretreatment.
[0080] The workpiece after surface pretreatment is placed in the composite polishing liquid. The polishing process includes polishing at normal temperature, polishing at heating, polishing at high temperature and polishing at normal temperature in sequence. The polishing temperature at normal temperature is room temperature and the polishing time is 30 minutes; the polishing temperature at heating stage is 40℃ and the polishing time is 50 minutes; the polishing temperature at high temperature is 80℃ and the polishing time is 40 minutes; the polishing temperature at normal temperature is room temperature and the polishing time is 18 minutes. During the polishing process, the stirring rate is 150rpm; after polishing, the GH3536 alloy workpiece is taken out to complete the polishing operation.
[0081] The composite polishing liquid is obtained by mixing a mixed acid solution, EDTA, ethylene glycol and a surfactant, and the volume mass ratio is 1L: 6g: 15g: 5g; the mixed acid solution is composed of 85% (v:v) H 3 PO 4 solution, 1.19 g / mL HCl solution and 1.41 g / mL HNO 3 The solution is mixed in a volume ratio of 1:7:4; the surfactant is sodium fatty alcohol ether sulfate / sodium dodecylbenzene sulfonate (v:v=4:1).
[0082] Example 2
[0083] The laser additively manufactured GH3536 alloy workpiece was cleaned, then placed in an acetone solution for ultrasonic cleaning and degreasing, and then degreasing with alcohol. After degreasing, it was washed with water and dried to complete the surface pretreatment.
[0084] The workpiece after surface pretreatment is placed in the composite polishing liquid. The polishing process includes polishing at normal temperature, polishing at heating, polishing at high temperature and polishing at normal temperature in sequence. The polishing temperature at normal temperature is room temperature and the polishing time is 45 minutes; the polishing temperature at heating stage is 50℃ and the polishing time is 30 minutes; the polishing temperature at high temperature is 100℃ and the polishing time is 30 minutes; the polishing temperature at normal temperature is room temperature and the polishing time is 25 minutes. During the polishing process, the stirring rate is 300rpm; after polishing, the GH3536 alloy workpiece is taken out to complete the polishing operation.
[0085] The composite polishing liquid is obtained by mixing a mixed acid solution, EDTA, ethylene glycol and sodium sulfate of fatty alcohol ether, and the volume mass ratio is 1L: 5g: 14g: 3g; the mixed acid solution is 85% (v:v) H 3 PO 4 solution, 1.19 g / mL HCl solution and 1.41 g / mL HNO 3 The solution was mixed in a volume ratio of 1:6.5:4.
[0086] Example 3
[0087] The laser additively manufactured GH3536 alloy workpiece was cleaned, then placed in an acetone solution for ultrasonic cleaning and degreasing, and then degreasing with alcohol. After degreasing, it was washed with water and dried to complete the surface pretreatment.
[0088] The workpiece after surface pretreatment is placed in the composite polishing liquid. The polishing process includes polishing at normal temperature, polishing at heating, polishing at high temperature and polishing at normal temperature in sequence. The polishing temperature at normal temperature is room temperature and the polishing time is 60 minutes; the polishing temperature at heating stage is 60℃ and the polishing time is 30 minutes; the polishing temperature at high temperature is 120℃ and the polishing time is 30 minutes; the polishing temperature at normal temperature is room temperature and the polishing time is 30 minutes. During the polishing process, the stirring rate is 450rpm; after polishing, the GH3536 alloy workpiece is taken out to complete the polishing operation.
[0089] The composite polishing liquid is obtained by mixing a mixed acid solution, EDTA, ethylene glycol and sodium sulfate of fatty alcohol ether, and the volume mass ratio is 1L: 6g: 12g: 2g; the mixed acid solution is composed of 85% (v:v) H 3 PO 4 solution, 1.19 g / mL HCl solution and 1.41 g / mL HNO 3 The solution was mixed in a volume ratio of 1:7.5:4.5.
[0090] Example 4
[0091] The laser additively manufactured GH4169 alloy workpiece was cleaned, then placed in an acetone solution for ultrasonic cleaning and degreasing, and then degreasing with alcohol. After degreasing, it was washed with water and dried to complete the surface pretreatment.
[0092] The workpiece after surface pretreatment is placed in the composite polishing liquid. The polishing process includes polishing at normal temperature, polishing at heating, polishing at high temperature and polishing at normal temperature in sequence. The polishing temperature at normal temperature is room temperature and the polishing time is 60 minutes; the polishing temperature at heating stage is 60℃ and the polishing time is 60 minutes; the polishing temperature at high temperature is 120℃ and the polishing time is 40 minutes; the polishing temperature at normal temperature is room temperature and the polishing time is 25 minutes. During the polishing process, the stirring rate is 450rpm; after polishing, the GH3536 alloy workpiece is taken out to complete the polishing operation.
[0093] The composite polishing liquid is obtained by mixing a mixed acid solution, EDTA, ethylene glycol and a surfactant, and the volume mass ratio is 1L: 8g: 12g: 4g; the mixed acid solution is composed of 85% (v:v) H 3 PO 4 solution, 1.19 g / mL HCl solution and 1.41 g / mL HNO 3 The solution is mixed in a volume ratio of 1:7.7:3.5; the surfactant is sodium fatty alcohol ether sulfate / sodium dodecylbenzene sulfonate (3:1).
[0094] Comparative Example 1
[0095] This comparative example uses mixed acid H 3 PO 4 -HCl-H 2 SO 4 The laser additively manufactured GH4169 alloy workpiece was polished, and other polishing conditions were the same as those in Example 1.
[0096] Comparative Example 2
[0097] This comparative example uses mixed acid H 3 PO 4 -HNO 3 -H 2 SO 4 The laser additively manufactured GH4169 alloy workpiece was polished, and other polishing conditions were the same as those in Example 1.
[0098] Comparative Example 3
[0099] This comparative example uses a hydrogen peroxide system polishing liquid HCl-H 2 O 2 The laser additively manufactured GH4169 alloy workpiece was polished, and the polishing conditions were the same as those in Example 1.
[0100] Comparative Example 4
[0101] This comparative example uses an alkaline system polishing liquid NaOH+KMnO 4 +H 2 The laser additively manufactured GH4169 alloy workpiece was polished, and the polishing conditions were the same as those in Example 1.
[0102] Compared with Example 1, Comparative Examples 1 and 2 use different mixed acids; the polishing liquid used in Comparative Examples 3 and 4 is different from the system of the composite polishing liquid used in Examples 1 to 4 of the present invention; after polishing, the roughness values of the fuel nozzle head component and the fuel nozzle overall component before and after chemical polishing are respectively detected, and the test results are shown in Table 1.
[0103] Table 1 Roughness values before and after polishing of Examples 1 to 4 and Comparative Examples 1 to 4
[0104]
[0105]
[0106] By comparison, it can be seen that after chemical polishing of the laser additively manufactured GH3536 alloy workpiece using the composite polishing liquid of the present invention, the roughness of the sample is significantly reduced, as shown in Figures 1 to Figure 3 The polishing liquid of Comparative Example 1 (whose mixed acid is H 3 PO 4 -HCl-H2 SO 4 ), the polishing liquid used in Comparative Example 1 (which uses a mixed acid H 3 PO 4 -HNO 3 -H 2 SO 4 ) After polishing of the laser additively manufactured GH3536 alloy workpiece, the roughness of the workpiece surface was not improved.
[0107] In addition, comparative example 3 uses a hydrogen peroxide system polishing liquid HCl-H 2 O 2 The laser additively manufactured GH4169 alloy workpiece was polished; Comparative Example 4 used an alkaline system polishing liquid NaOH+KMnO 4 +H 2 The laser additively manufactured GH4169 alloy workpiece was polished, and the test results were not ideal. After polishing, the roughness of the workpiece surface was not significantly improved.
[0108] In summary, the composite polishing liquid and the polishing method thereof of the present invention can reduce the roughness of the alloy surface and improve the smoothness and brightness of the alloy material.
[0109] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A composite polishing liquid for laser additive manufacturing of alloy materials, characterized in that: It includes mixed acid solution, masking agent, stabilizer and surfactant; The mixed acid solution is H3PO4-HCl-HNO3; The mass ratio of the mixed acid solution, the masking agent, the stabilizer and the surfactant is 1L: 5-8g: 12-18g: 2-5g.
2. The composite polishing liquid for laser additive manufacturing alloy materials according to claim 1, characterized in that: In the mixed acid solution, the volume ratio of H3PO4 solution, HCl solution and HNO3 solution is 1:(6.5-7.7):(3.5-4.5).
3. The composite polishing liquid for laser additive manufacturing alloy materials according to claim 2, characterized in that: The volume concentration of the H3PO4 solution is 80-85%; The mass concentration of the HCl solution is 1.15-1.2 g / mL; the mass concentration of the HNO3 solution is 1.4-1.45 g / mL.
4. The chemical polishing method for laser additive manufacturing alloy materials according to claim 3, characterized in that: The preparation method of the mixed acid solution H3PO4-HCl-HNO3 is to mix H3PO4 solution, HCl solution and HNO3 solution in sequence.
5. The composite polishing liquid for laser additive manufacturing alloy materials according to claim 1, characterized in that: The masking agent includes one or more of EDTA, citric acid and tartaric acid.
6. The composite polishing liquid for laser additive manufacturing alloy materials according to claim 1, characterized in that: In step 2, the stabilizer includes one or more of ethanol, ethylene glycol, propylene glycol and diethylene glycol.
7. The composite polishing liquid for laser additive manufacturing alloy materials according to claim 1, characterized in that: The surfactant includes one or more of sodium fatty alcohol ether sulfate, betaine type amphoteric surfactant and sodium dodecylbenzene sulfonate.
8. A method for polishing alloy materials produced by laser additive manufacturing, characterized in that: The composite polishing liquid according to any one of claims 1 to 7 is used; the polishing method comprises the following steps: Step 1, pre-treating the surface of the laser additively manufactured alloy material; Step 2, measuring the mass and roughness of the sample before chemical polishing, and observing its morphology with a microscope; Step 3: Mix the laser additive manufacturing alloy material after surface pretreatment with the composite polishing liquid, and perform polishing treatment to achieve polishing of the laser additive manufacturing alloy material.
9. The polishing method of alloy material manufactured by laser additive manufacturing according to claim 8, characterized in that: In the step 1, the pretreatment includes cleaning, degreasing and water washing in sequence.
10. The polishing method of alloy material manufactured by laser additive manufacturing according to claim 9, characterized in that: The laser additive manufacturing alloy material includes GH3536 alloy or GH4169 alloy.
Citation Information
Patent Citations
Chemical polishing liquid used for metal and polishing technology
CN105714299A
Polishing solution for chemico-mechanical polishing of lead, and anti-oxidation technology thereof
CN110564303A
Stainless steel polishing agent as well as preparation method and application thereof
CN110846665A
Environment-friendly copper chemical polishing brightener and preparation method thereof
CN118516675A
Fast chemical grinding polishing bath liquid for stainless steel surface and its method
CN1724707A
